MICROBIAL STATUS OF DONKEY’S MILK: FIRST RESULTS - L. Alberghini (Italian Journal of Food Safety, 2012)
For its chemical and nutritional composition donkey milk is an excellent substitute for human breast milk. In fact, woman’s milk and donkey one are quite similar for their composition and for certain intrinsic properties. Based on these considerations, we performed a study on the microbiological characteristics of 86 jannet’s milk in 10 farms. Special attention was given to the aspects of health quality of the milk samples examined, referring to the analysis of total microbial count and pH, the possible presence of potentially pathogenic micro-organisms, especially by seeking the bacteria Escherichia coli O157, Salmonella spp., Listeria monocytogenes and Campylobacter spp. The samples of milk were picked up from January to March 2010. Our research showed a situation quite positive in terms of sanitation, finding levels of total microbial count (on average 1,8·104 cfu/ml) and pH (mean 7,02) entirely in line with data found in previous investigations of other Authors and with values reassuring in terms of healthiness of the product. Regarding the detection of potentially pathogenic microorganisms, only a milk sample of 86 tested was positive for E. coli O157; in an other sample low charges of Campylobacter spp. have been measured. Salmonella spp. and Listeria monocytogenes were not found in all samples. Total microbial count confirm the good quality of the donkey milk. However, occasional isolation of E. coli O157 and Campylobacter spp. suggests careful attention is to be done to the correct procedures of milking hygiene.